1971
DOI: 10.1085/jgp.58.4.372
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Duck Erythrocytes to Nonhemolytic Hypotonic Media

Abstract: Duck erythrocytes were incubated in hypotonic media at tonicities which do not produce hemolysis. The cells' response can be divided into two phases: an initial rapid phase of osmotic swelling and a second more prolonged phase (volume regulatory phase) in which the cells shrink until they approach their initial isotonic volume. Shrinkage associated with the volume regulatory phase is the consequence of a nearly isosmotic loss of KCI and water from the cell. The potassium loss results from a transient increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
3
2

Year Published

1973
1973
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(124 citation statements)
references
References 18 publications
10
108
3
2
Order By: Relevance
“…Sutton-Jones and Street (28) also showed that in cell suspensions ofAcerpseudoplatanus the cytoplasm reaches its maximum thickness in the early stages of the cell division phase, but they gave no quantitative data. In the present culture, cells on a 7-day cycle never become highly vacuolated, but if the culture is continued for a longer time, the vacuole volume reached 90%7b of the cell volume by day 12 ( Fig. 3).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Sutton-Jones and Street (28) also showed that in cell suspensions ofAcerpseudoplatanus the cytoplasm reaches its maximum thickness in the early stages of the cell division phase, but they gave no quantitative data. In the present culture, cells on a 7-day cycle never become highly vacuolated, but if the culture is continued for a longer time, the vacuole volume reached 90%7b of the cell volume by day 12 ( Fig. 3).…”
Section: Resultsmentioning
confidence: 54%
“…For instance, it has been suggested that the volume of wallless cells may be sensed by the tension of the plasma membrane (11,12), but this concept is less simple in vacuolate cells, where the tension of the tonoplast presumably depends more on the volume ofthe vacuole than on the volume ofcytoplasm. Moreover, current concepts of volume regulation focus on adaptation to environmental changes, but largely ignore the question of how the cytoplasmic volume keeps pace with other cellular growth processes.…”
Section: Resultsmentioning
confidence: 99%
“…The procedures for obtaining LSS cells ([K], 110 mmol/liter, [Na], -5 mmol/liter, and [Cl], 51 mmol/liter) has been described elsewhere (1,2).…”
Section: Methodsmentioning
confidence: 99%
“…1 in reference [1]). This same reference (1) also contains a description of the procedures for measuring the rate of 24 Na and 42K loss from cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation